Yellow fever vector live-virus vaccines: West Nile virus vaccine development - Arroyo, Juan (Trends Mol Med, 2001)
By combining molecular-biological techniques with our increased understanding of the effect of gene sequence modification on viral function, yellow fever 17D, a positive-strand RNA virus vaccine, has been manipulated to induce a protective immune response against viruses of the same family (e.g. Japanese encephalitis and dengue viruses). Triggered by the emergence of West Nile virus infections in the New World afflicting humans, horses and birds, the success of this recombinant technology has prompted the rapid development of a live-virus attenuated candidate vaccine against West Nile virus.